Knockdown of Hsc70-5/mortalin induces loss of synaptic mitochondria in a Drosophila Parkinson's disease model. - Jun-Yi Zhu; Natalia Vereshchagina; Vrinda Sreekumar; Lena F Burbulla; Ana C Costa; Katharina J Daub; Dirk Woitalla; L Miguel Martins; Rejko Krüger; Tobias M Rasse (PLoS ONE)
Mortalin is an essential component of the molecular machinery that imports nuclear-encoded proteins into mitochondria, assists in their folding, and protects against damage upon accumulation of dysfunctional, unfolded proteins in aging mitochondria. Mortalin dysfunction associated with Parkinson's disease (PD) increases the vulnerability of cultured cells to proteolytic stress and leads to changes in mitochondrial function and morphology. To date, Drosophila melanogaster has been successfully used to investigate pathogenesis following the loss of several other PD-associated genes. We generated the first loss-of-Hsc70-5/mortalin-function Drosophila model. The reduction of Mortalin expression recapitulates some of the defects observed in the existing Drosophila PD-models, which include reduced ATP levels, abnormal wing posture, shortened life span, and reduced spontaneous locomotor and climbing ability. Dopaminergic neurons seem to be more sensitive to the loss of mortalin than other neuronal sub-types and non-neuronal tissues. The loss of synaptic mitochondria is an early pathological change that might cause later degenerative events. It precedes both behavioral abnormalities and structural changes at the neuromuscular junction (NMJ) of mortalin-knockdown larvae that exhibit increased mitochondrial fragmentation. Autophagy is concomitantly up-regulated, suggesting that mitochondria are degraded via mitophagy. Ex vivo data from human fibroblasts identifies increased mitophagy as an early pathological change that precedes apoptosis. Given the specificity of the observed defects, we are confident that the loss-of-mortalin model presented in this study will be useful for further dissection of the complex network of pathways that underlie the development of mitochondrial parkinsonism.